Prothrombin Synthesis in the Adult and Fetal Liver - Cohen, Leon; McKinnell, James; Puglisi, Vincent; Greco, Alba; Nardi, Michael; Lee, Margaret; Karpatkin, Margaret (Thrombosis and Haemostasis, 1997)
Plasma levels of blood coagulation zymogens are lower in the newborn than in the adult, with the lowest levels being in preterm infants. It is not known if the lower coagulation factor levels reflect differences in synthesis, secretion or catabolism.Using a rabbit model we have compared prothrombin synthesis in the fetus and adult. In previous studies we attempted to compare transcription in the adult and fetal liver by extraction of mRNA, immobilization on a membrane and hybridization with a labeled cDNA for rabbit prothrombin. Comparison was impaired by the markedly dissimilar composition of fetal and adult rabbit liver; fetal liver is approximately fifty percent hematopoietic tissue even at term (1). In the present study, to obtain a more meaningful comparison we have employed in situ hybridization to compare directly prothrombin expression in adult and fetal liver. We report here that fetal liver contains more prothrombin mRNA than does adult liver. We have further compared prothrombin levels in protein extracts of adult and fetal liver and found that per microgram of extract, fetal liver contains as much prothrombin as does the adult. We conclude that the lower plasma prothrombin levels in the fetus do not reflect a lower rate of synthesis.